1998
DOI: 10.1111/1469-7610.00401
|View full text |Cite
|
Sign up to set email alerts
|

Trick or Treat?: Uneven Understanding of Mind and Emotion and Executive Dysfunction in “Hard‐to‐manage” Preschoolers

Abstract: It is widely recognised that impaired social relations are characteristic of school-aged children with behavioural disorders, and predict a poor long-term outcome (Parker & Asher, 1987). However, little is known about the early antecedents of social impairment in behaviourally disturbed children. The aim of the present study was to explore three areas of potential dysfunction in younger children: theory of mind, emotion understanding, and executive function. Forty preschoolers, rated by their parents on the St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
198
4
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(226 citation statements)
references
References 48 publications
(60 reference statements)
18
198
4
6
Order By: Relevance
“…It is possible, for example, that children with poor verbal abilities may be at a disadvantage in performing tasks that rely on verbal responses. Previous research suggests that poor verbal ability may play a role in the facial emotion-recognition difficulties seen in preschoolers with externalizing symptoms (Hughes, Dunn, & White, 1998), and future research should include verbal ability measures in emotionrecognition tasks that rely on verbal responses. The stimuli used in the current study might also account for the pattern of results.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, for example, that children with poor verbal abilities may be at a disadvantage in performing tasks that rely on verbal responses. Previous research suggests that poor verbal ability may play a role in the facial emotion-recognition difficulties seen in preschoolers with externalizing symptoms (Hughes, Dunn, & White, 1998), and future research should include verbal ability measures in emotionrecognition tasks that rely on verbal responses. The stimuli used in the current study might also account for the pattern of results.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies (9/11) have found a significant association between ADHD symptoms and deficient behavioral inhibition (Berlin & Bohlin, 2002;Berlin et al, 2003;Byrne, DeWolfe, & Bawden, 1998;Campbell et al, 1982Campbell et al, , 1994Hughes, Dunn, & White, 1998;Marakovitz & Campbell, 1998;Sonuga-Barke et al, 2002;Sonuga-Barke, Dalen, & Remington, 2003), adding credence to the hypotheses that early behavioral inhibition predicts later ADHD symptoms and may influence the relationship between early and later ADHD symptoms.…”
Section: Studies Of Inhibition and Adhd Symptoms In Childrenmentioning
confidence: 96%
“…At four years (corrected age), EF was assessed using a modified version of the Detour Reaching Box (DRB) Task (Hughes et al, 1998;Hughes & Russell, 1993). This task provides a measure of inhibitory control (i.e., the ability to inhibit a prepotent, salient response) and the ability to switch effectively from a previously reinforced rule.…”
Section: Assessment At Age Four Years (Corrected)mentioning
confidence: 99%